Estimation of Land Surface Temperature for Different Regions in Iraq Using Remote Sensing Technique (ETM+) - Yaseen K. Al-Timimi yassen-atimimi; Ali M. Al-Salihi; Alaa M. Al-lami (Engineering and Technology Journal, 2014)
Temperatures are important factors that have an impact directly and indirectly on human, so the attention to this aspect certainly will be in the interest of human life. In this research, the land surface temperature was estimated for different regions in Iraq, using the thermal Band of ETM+ sensor mounted in the Landsat 7 satellite. By using ERDAS 8.4 software, the thermal images are converted to thematic maps which represent land surface temperatures. The results showed that the estimated land surface temperatures are 29.7°C, 31.8°C, 17°C, 17.8°C, 17°C, 20.6°C and 30.2°C for Al-Mousl , Taleafer, Al-Ramadi, Heet, Kerbela, Al-Hai and Al-Basrah stations respectively. Also the results show that there is high correlation between the estimated and the observed data with a difference of 1-2°C.